Rainfall effects on Anomalocardia flexuosa densities on the northeastern Brazilian coast using distributed lag models - Severino Adriano de Oliveira Lima; Humber Agrelli Andrade; Raniere Garcez Costa Sousa (Boletim do Instituto de Pesca)
In this study, the effects of precipitation on Anomalocardia flexuosa densities were analyzed from the perspective of temporal delays between the variables. The collections occurred bi-monthly between April 2016 and February 2018 at Mangue Seco beach, Pernambuco, Brazil. Total densities and densities according to the category of size (small, medium and large), and precipitation were analyzed with autocorrelation and cross-correlation functions, with a retrospective analysis of up to 12 months. Distributed lag models were used among the variables. The maximum density was found in June 2017 (378 ind.m2) for the medium-size category of individuals. Significant autocorrelations occurred for densities (total and average size) and precipitation. In cross-correlation functions, high precipitation for a given month was followed by high densities of total and average individuals for up to two months. Distributed lag models also showed significant values between densities (total and medium-sized) and precipitation, which explained more than 50% of the variability of these two groups. The effect of precipitation was responsible for the increase in the density of A. flexuosa for up to two months, mainly by increasing individuals with medium shell lengths.